Fairness and Climate Change - Singer, Peter; Fei, Teng (Revista Hipótese, 2022)
Peter Singer’s articles regularly appear in Brazil in O Estado de São Paulo, courtesy of Project Syndicate (www.project-syndicate.org). This article is a translation by Ivan Fortunato, Ph.D., of “Fairness and Climate Change” which first appeared in Project Syndicate, in 2013.